PERJANJIAN PENGELOLAAN HAK GUNA USAHA (STUDI KASUS KERJASAMA ANTARA KOPERASI TUAH SEKATO DENGAN PT ARARA ABADI) - Ni Ketut Sri Parwati; Mr. Sudjito (Fakultas Hukum Universitas Gadjah Mada, 2008)
Management of forest plant with partnership pattern was not fair and did not provide welfare to community. Low education, lack of legal knowledge and less support from government have deprived sense of justice of local community. This research used literary study as main supporting material and field study to collect secondary material to complete this research. Data obtained from literary and field study was analyzed qualitatively and its result was described to get objective description.